Plan de negocios para la factibilidad de la microempresa de yogurt artesanal “Yogurt Don Robert” del cantón Chone - Castro Acosta, Julexi Andreina (2025)
This study was conducted with the purpose of developing a business plan to position Don Roberth yogurt in Chone Canton. It is important to highlight that this tool significantly contributed to the company by allowing the structuring of planned ideas, facilitating the organization of projects, and making the business a reality once the stages that form its structure were completed. To carry out this process, four phases were defined. The first phase involved a situational study to analyze the macro and micro aspects of the business. In the second phase, a survey was conducted, making the use and application of well-structured questionnaires essential. This facilitated data collection on events, consumption behaviors, opinions, and habits of local residents, resulting in the product's acceptance by the public. Additionally, a technical-operational study was required to define the costs, materials, and supplies necessary to launch the company. The third phase consisted of an economic-financial analysis, which allowed the determination of the project's profitability and viability, yielding a positive Internal Rate of Return (IRR) that exceeds the discount rate, as well as a favorable Net Present Value (NPV). Finally, the fourth phase involved an environmental analysis related to the business's production.